Level of Awareness on the Impact of Climate Change on the Socioeconomic Life of a Coastal Community in San Salvador Island, Masinloc, Zambales - Vizcarra, Myra Liza O. (Future Science / FSH-PH Publications, 2023)
The researcher’s interest in their well-being led her to study the level of awareness of the impact of climate change on the socioeconomic life of the coastal communities in San Salvador Island. This study is a descriptive type of research. A descriptive study gives a picture and describes the different aspects concerning a situation to obtain knowledge of nature, states, and development. This current study was conducted at San Salvador Island. It is an island barangay in Masinloc, Zambales, in northwest Luzon. It is an island barangay in Masinloc, Zambales, in northwest Luzon. A 127-hectare fish sanctuary and a nearby Taklobo or Giant Clam Farm are usual attractions to diving enthusiasts. Encourage planting mangroves in the vicinity of the island as part of the extension service of the campus. Conduct a follow-up study on fishermen’s vulnerability, resiliency, and mitigation practices. They are considered priority barangay in the Climate Change Awareness joint project of the PRMSU-Masinloc LDRRMP and CENRO-Masinloc to enhance the fishermen’s awareness and adaptation. Support from the local government unit by having a store filled with more goods and over-the-counter medicines, especially during rainy seasons. May have a routine check by a professional doctor before rainy seasons. Probable additional livelihood to augment needs, particularly during the rainy season.